EFEKTIVITAS PENGAWASAN PEMBANGUNAN PERMUKIMAN DI KOTA PEKANBARU - Yunika Sari; Zaili Rusli SD (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Development is one of the most important aspects in a country. Development here is not only physical such as office buildings or physical infrastructure. But the intended development is various aspects of life, such as physical development, social development, economic development and many other developments. Likewise for city development which has not much different definitions for national development in general. In the development of settlement construction, precisely in the city of Pekanbaru, so far there have been many complicated problems. The purpose of this study was to determine the effectiveness of supervision of settlement development in Pekanbaru city and to find out the factors that influence the effectiveness of supervision of settlement development in Pekanbaru City. The theory used in this study is the effectiveness of supervision, settlement construction, spatial concepts. After conducting research, it was found that the effectiveness indicators of the supervision of settlement construction in Pekanbaru City were input, process, output, outcome. The factors that influence the effectiveness of supervision of settlement development in Pekanbaru are human resources and infrastructure inadequate as well as limitations and budget. The conclusion of the effectiveness of development supervision is that supervision by the office of spatial planning and building in carrying out its duties and functions is still not fully implemented, because there still need to be some improvements that must be considered. Keywords : Effectiveness of Settlement Supervision and Development